Serum leptin and its relation to body composition, puberty, and metabolism in severe obesity - Sabina Galiniak; Marek Biesiadecki; Rafał Podgórski; Natalia Dąbek; Ewa Gramatyka-Drążek; Ewelina Gaweł; Michael B Ranke; Bertram Flehmig; Martin Wabitsch; Stephanie Brandt; Elżbieta Petriczko; Małgorzata Wójcik; et al. (Endocrine Connections)
Childhood severe obesity (SO) is a growing public health concern. Leptin (LEP) and its biologically active fraction (BioLEP) play a key role in energy balance and body mass regulation. Understanding their relationship with anthropometric and metabolic parameters is crucial for improving SO treatment. This study analyzed total LEP, BioLEP, and the BioLEP/LEP ratio in children with SO and their associations with body composition, lipid profile, and pubertal development. The study included 461 children (245 girls and 216 boys) aged 0–19 years with SO. Anthropometric parameters, metabolic indices, and pubertal stages (Tanner scale) were assessed. LEP and BioLEP concentrations were measured using ELISA, and the BioLEP/LEP ratio was calculated. The median LEP concentration was 56.53 ng/mL, and BioLEP was 53.66 ng/mL, with a BioLEP/LEP ratio of 0.94. Girls had significantly higher LEP (64.40 vs 49.66 ng/mL, P < 0.001) and BioLEP (59.90 vs 46.93 ng/mL, P < 0.001) than boys. LEP and BioLEP correlated positively with BMI, waist and hip circumference, and fat mass percentage, while negatively with waist-to-hip ratio and fat-free mass. The BioLEP/LEP ratio correlated positively with insulin and lipid profile parameters (total cholesterol, HDL, and triglycerides). LEP and BioLEP play a significant role in SO, particularly in fat mass regulation. The BioLEP/LEP ratio is more closely linked to lipid metabolism. These findings provide insights into the hormonal and metabolic profile of SO, supporting targeted diagnostic and therapeutic approaches.